The Impact of Online Consumer Review to Online Hotel Booking Intention in Malaysia - Lian Fong Stany Wee; Tan Pei Kian; Yeo Sook Fern; Soh Long Quan (International Journal of Supply Chain Management, 2018)
Travellers today tend to believe more on peer reviews in selecting tourism products and services instead of information provided by the businesses. With the rise of communication technologies such as Web 2.0, there is pool of opinions on hotels, tourism destinations, and even travel services that are expressed from the perspective of consumer consumption in the internet. As online review becomes an important source for travellers to evaluate the quality of hospitality services, only hoteliers that take advantage of online review are able to attract the attention of travellers that utilize the digital channel for information searching. The increment of hotels and rooms in Malaysia has somehow exceed the increment of tourist arrivals in the recent years. Hoteliers are worried that the supply would go beyond the demand in the future with the continuous growth of hotels but average occupancy rate remains at 62 to 63 percent. Thus, this study aims to examine the causal relationship between the attributes of the online consumer reviews and the online hotel booking intention specifically in Malaysia context. 200 survey responses were collected from local travellers that have at least once booked hotel through online method. The results show that usefulness (t = 3.478, p 0.01), valence (t = 2.462, p 0.05), and timeliness (t = 2.145, p 0.05) of the online consumer review significantly affect the online hotel booking intention in Malaysia. This findings provide an insight to hoteliers on how to manage and improve the online consumer reviews that are accessible.